En opgørelse af boligformuen - Jan Overgaard Olesen; Erik Haller Pedersen (Danmarks Nationalbank, 2006)
– Based on data on the living space of dwellings compiled by Statistics Denmark and data on housing prices compiled by Realkreditraadet (the Association of Danish Mortgage Banks), we calculate three measures of housing wealth for Denmark in the period from 1981 to 2006. These measures include total housing wealth, the housing wealth of households and the value of owner-occupied homes with a breakdown by type of dwelling (detached one-family houses, terraced houses, farmhouses, freehold flats, holiday dwellings and multi-family buildings excluding freehold flats). This paper provides a documentation of methodology and presents results. Moreover, we apply the wealth figures when calculating capital gains on housing and the amount of non-mortgaged housing wealth of households (home-equity). Finally, we discuss alternative housing wealth measures that are publicly available.
Keywords: 330; housing wealth; capital gains; home-equity